BMI and pneumonia outcomes in critically ill COVID‐19 patients: An international multicenter study. Issue 9 (24th August 2021) - Chetboun, Mikael; Raverdy, Violeta; Labreuche, Julien; Simonnet, Arthur; Wallet, Florent; Caussy, Cyrielle; Antonelli, Massimo; Artigas, Antonio; Goma, Gemma; Meziani, Ferhat; Helms, Julie; Mylonakis, Eleftherios; et al.
Abstract: Objective: Previous studies have unveiled a relationship between the severity of coronavirus disease 2019 (COVID‐19) pneumonia and obesity. The aims of this multicenter retrospective cohort study were to disentangle the association of BMI and associated metabolic risk factors (diabetes, hypertension, hyperlipidemia, and current smoking status) in critically ill patients with COVID‐19. Methods: Patients admitted to intensive care units for COVID‐19 in 21 centers (in Europe, Israel, and the United States) were enrolled in this study between February 19, 2020, and May 19, 2020. Primary and secondary outcomes were the need for invasive mechanical ventilation (IMV) and 28‐day mortality, respectively. Results: A total of 1, 461 patients were enrolled; the median (interquartile range) age was 64 years (40.9‐72.0); 73.2% of patients were male; the median BMI was 28.1 kg/m 2 (25.4‐32.3); a total of 1, 080 patients (73.9%) required IMV; and the 28‐day mortality estimate was 36.1% (95% CI: 33.0‐39.5). An adjusted mixed logistic regression model showed a significant linear relationship between BMI and IMV: odds ratio = 1.27 (95% CI: 1.12‐1.45) per 5 kg/m 2 . An adjusted Cox proportional hazards regression model showed a significant association between BMI and mortality, which was increased only in obesity class III (≥40; hazard ratio = 1.68 [95% CI: 1.06‐2.64]). Conclusions: In critically ill COVID‐19 patients, a linear association between BMI and the need for IMV, independent of other metabolic risk factors, and a nonlinear association between BMI and mortality risk were observed.